Development Of Speed-Strength Skills (Eurasian Scientific Herald, 2024)
In this article, it is mentioned that the effectiveness of any movement (running, jumping, sitting, hanging, throwing, exercises in gymnastic shells, etc.) is related to the strength of the athlete in training the qualities of strength and strength-speed.